The Geology Of Montana Talc Deposits - Richard H. Olson (Society for Mining, Metallurgy & Exploration, 1975)
Talc deposits in the Precambrian of southwestern Montana (Beaverhead and Madison Counties) are unique within the U. S. A. in that large bodies of tremolite-free talc can be open-pit mined. All known deposits are in pre-Beltian dolomite units. The origin is suspected to be metasomatic, with the siliceous component having been contributed by an intrusive Precambrian granite gneiss. Precambrian deformation was extreme and is characterized by multiple periods of tight isoclinal folding and the flowage of less competent rocks, rather than by faulting. Post- Precambrian folding has been relatively negligible; the characteristic Laramide structure is block-faulting developed along northwest-southeast trends. The talc is thought to have been formed in Precambrian time; the high-angle block-faults probably have no significance with regard to the formation of the talc, but do tend to complicate mining operations. Tremolite-free talc ore bodies with horizontal widths of more than 200 feet, vertical depths of several hundreds of feet, and strike-lengths of as much as one-half mile are known in the Ruby Range and the Gravelly Range. Where dolomite is interbedded with tremolite-free talc in the Gravelly Range, the scale of this relationship permits the use of conventional open-pit mining methods with subsequent upgrading by hand-sorting techniques. Underground mining has been used in the past, but all current Montana talc-mining operations are on the surface. The hand-sorted ore, some of which is shipped overseas, is finely ground or micronized in roller mills and fluid-energy mills. The products are distributed both nationwide and abroad.